The Effect of Fluid Composite as Gingival Layer on Microleakage of Class II Composite Restorations - M. Sadeghi (Wolters Kluwer Medknow Publications, 2007)
Introduction: Fluid composites have been suggested as gingival layer beneath class II composite restorations to improve marginal integrity and reduce microleakage. This in-vitro study evaluated the influence of fluid composites as gingival layer on microleakage of class II packable, microhybrid, and fiber-reinforced composite restorations with the margins below the cementoenamel junction (CEJ).Methods and Materials: 45 sound premolars extracted for orthodontic reasons were selected. Class II cavities were prepared on the mesial and distal aspects with the gingival margin placed 1 mm below the CEJ, making 90 slot cavities. Teeth were randomly assigned into 3 groups (n=15). In each group, one side of each tooth was restored incrementally with respective packable, microhybrid, and fiber-reinforced composites; whereas, on the other side, fluid composite was placed as a 1 mm thickness gingival increment before restoration with the same composites. The teeth were stored for one week in distilled water at 37$C, thermo-cycled (5-55$C, x 1500), and immersed in 0.5% basic fuchsine for 24 hours. Dye penetration was evaluated using a stereomicroscope at 10x magnification. The data were analyzed statistically by Kruskal-Wallis analysis of variance and Mann-Whitney U-test.Results: The fluid composite reduced microleakage at gingival margins of Class II restorations (P<0.05). The packable composite with or without fluid composite- showed lower microleakage, whereas microhybrid and fiber-reinforced composites without fluid composite, showed higher microleakage.Discussion: The fluid composite significantly decreased the microleakage at gingival margins of Class II composite restorations.